AUDIT MANAJEMEN INOVASI TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 DOMAIN APO04 PADA JT DIGITALLY - Melinne Maldini Rosady; Ika Ima Nissa; Leo Sandi (Journal of Innovation And Future Technology, 2026)
In the current digital era, Information Technology has evolved beyond its traditional role as a mere supporting function and has become a strategic core that drives organizational competitiveness. Effective data governance is essential to improving data management practices, which ultimately contributes to enhanced organizational performance. JT Digitally is a company specializing in digital marketing agency services, offering solutions including digital marketing, software product development, and technology services. This study employs the COBIT 2019 Framework as its primary evaluation instrument, selected due to its focus on assessing capability and maturity levels based on designated target domains. The APO04 domain is employed to evaluate the company's Innovation Management System, encompassing the establishment and communication of quality standards across all relevant processes, procedures, and organizational outcomes. This research formulates strategic recommendations derived from the IT governance evaluation conducted at JT Digitally using the COBIT 2019 framework, specifically the APO04 domain. The capability assessment of APO04 subdomains shows an average score of 2.6 (Partially Achieved), indicating that implementation has begun but requires further strengthening. Recommendations include developing innovation governance policies and procedures, client-centered innovation management, and a systematic documentation